Genetic parameters and correlation studies in Indian mustard (Brassica juncea L.) - RR Choudhary; R Avtar; M Singh; M Bishnoi (Journal of Oilseed Brassica, 2026)
Present study carried out with total 154 genotypes including 150 test genotypes and four checks (RH-1566, RH-1499-30,RH-749 and RH-8812) of Indian mustard. These genotypes were evaluated for seed yield and its yield components foreleven characters during rabi season of 2020-21 at CCS Haryana Agricultural University, Hisar. Analysis of varianceshowed highly significant genotypic difference for all the studied traits. The maximum variability (21.2%) was recordedfor test weight and minimum for oil content (0.8%). The two characters namely, secondary branches/plant (91.7%) andtest weight (89.6%) had very high broad sense heritability while, genetic advance was relatively high for test weight(41.4%), number of secondary branches/plant (37.2%) and seed yield/plant (31.6%). The results revealed that plantheight, number of primary branches/plant, number of secondary branches/plant, main shoot length, number of siliqua onmain shoot, siliquae length, number of seeds per siliqua and test weight have significant positive association with seedyield/plant, while path analysis revealed that number of primary branches/plant, number of secondary branches/ plantand siliqua length had the highest positive direct effects on seed yield/plant. All the traits have showed high heritability.The characters identified above as indirect yield components in formulating effective selection strategy for developinghigh yielding mustard genotypes.